An Effective Pt-Cu/SiO2 Catalyst for the Selective Hydrogenation of Cinnamaldehyde - Dong Wang; Yujun Zhu (Journal of Chemistry)
The bimetal catalyst Pt-Cu/SiO2 was prepared by the impregnation method. Its catalytic performance was investigated by the selective hydrogenation of cinnamaldehyde. Pt-Cu/SiO2 exhibited much higher selectivity (64.1%) to cinnamyl alcohol than Pt/SiO2 (3.7%), while they showed similar conversion of cinnamaldehyde. This enhancement was attributed to the increase in the amount of the Pt0 species on the Pt-Cu/SiO2 surface, which is derived from the interaction between Pt and Cu revealed by XRD and XPS.